Fear of movement and (re)injury is associated with condition specific outcomes and health-related quality of life in women with patellofemoral pain - Pazzinatto, Marcella F. [UNESP]; Silva, Danilo De Oliveira [UNESP]; Willy, Richard W.; Azevedo, Fábio M. [UNESP]; Barton, Christian J. (Taylor & Francis, 2020)
Objectives: Investigate the association of fear of movement and (re)injury with clinical outcomes in women with patellofemoral pain (PFP). Methods: This cross-sectional study included 92 women with PFP who completed the TAMPA scale for kinesiophobia. The TAMPA score and its two subscales–activity avoidance and somatic focus were correlated with BMI, physical activity level, pain catastrophizing scale, health-related quality of life, pain sensitivity via pressure pain threshold, self-reported disability, and worst knee pain in last month. Results: Greater fear of movement and (re)injury, activity avoidance, and somatic focus were correlated with lower local pain sensitivity (rho = −0.29 to −0.55), lower health-related quality of life (rho = −0.38 to −0.42), greater pain catastrophizing (rho = 0.41 to 0.47), and greater self-reported disability (rho = −0.31 to −0.52). Greater fear of movement and (re)injury and activity avoidance were correlated with adjacent and remote pain sensitivity (rho = −0.24 to −0.39). Greater fear of movement and (re)injury and somatic focus were correlated with greater worst knee pain in last month (rho = 0.21 to 0.32). Fear of movement and (re)injury predicted pain measures, disability, and health-related quality of life (p ≤ 0.010). Conclusion: The relationship of greater fear of movement and (re)injury with greater disability, pain catastrophizing, pain sensitization, and poorer health-related quality of life highlights the potential importance of considering this psychological feature of PFP during assessment and management.
Keywords: avoidance behavior; hyperalgesia; kinesiophobia; Knee; physical functional performance